Problem-based learning in the online flipped classroom: Its impact on statistical literacy skills - Domu, Ichdar; Pinontoan, Kinzie Feliciano; Mangelep, Navel Oktaviandy (Journal of Education and e-Learning Research, 2023)
This study aimed to improve students' literacy skills in carrying out distance learning and examine the effect of problem-based learning in reverse online classes on statistical literacy skills in distance learning. This research was conducted during the COVID-19 pandemic at Prisma University and Manado State University with 198 students taking statistical methods courses. A quantitative approach to quasi-experimental research was used. The instruments used are written tests and video-based projects with relevant entrepreneurship questions. Data was collected through pre- and post-tests, then analyzed using a two-way Analysis of Variance (ANOVA) and an independent sample t-test. The results showed that problem-based learning in reverse online classes positively affected statistical literacy skills in distance learning. In addition, positive responses from students working on statistical projects in entrepreneurship were found. This may be observed from the perceptions of students who show high satisfaction with the assignment in the field of entrepreneurship in this study. Furthermore, the results of this study confirm that student involvement is a critical element in implementing distance learning.